Early Life Wheeze and Risk Factors for Asthma-A Revisit at Age 7 in the GEWAC-Cohort - Idun Holmdahl; Anastasia Filiou; Katarina Stenberg Hammar; Anna Asarnoj; Magnus P. Borres; Marianne van Hage; Gunilla Hedlin; Cilla Söderhäll; Jon R. Konradsen (MDPI AG, 2021)
One third of all toddlers are in need of medical care because of acute wheeze and many of these children have persistent asthma at school age. Our aims were to assess risk factors for and the prevalence of asthma at age 7 in a cohort of children suffering from an acute wheezing episode as toddlers. A total of 113 children, included during an acute wheezing episode (cases), and 54 healthy controls were followed prospectively from early pre-school age to 7 years. The protocol included questionnaires, ACT, FeNO, nasopharyngeal virus samples, blood sampling for cell count, vitamin D levels, and IgE to food and airborne allergens. The prevalence of asthma at age 7 was 70.8% among cases and 1.9% among controls (p < 0.001). Acute wheeze caused by rhinovirus (RV) infection at inclusion was more common among cases with asthma at age 7 compared to cases without asthma (p = 0.011) and this association remained significant following adjustment for infection with other viruses (OR 3.8, 95% CI 1.4-10.5). Cases with asthma at age 7 had been admitted to hospital more often (p = 0.024) and spent more days admitted (p = 0.01) during the year following inclusion compared to cases without asthma. RV infection stands out as the main associated factor for wheeze evolving to persistent asthma. Cases who developed asthma also had an increased need of hospital time and care for wheeze during the year after inclusion.